Allah made them all: quran stories for little hearts - Lockhat, Khadija; Negi, Devender (Goodword Books New Delhi, 2004)
A child learns about the diversity of creation, recognizing that every creature reflects Allah$1 (Bs wisdom and artistry in the world.s